A review of chemical constituents from Ajuga nipponensis and their anti-inflammatory activities analysis. (December 2022) - Sun, Na; Yang, Huanhuan; Zhou, Miao; Hou, Yanyan; Wu, Xinru; Li, Wenqian; Liu, Hui; Zheng, Lijie; Sun, Jinge; Jin, Linxuan; Ma, Shuo; Shu, Penghua
Abstract: Fifteen ecdysterones, thirty-six diterpenoids, four flavonoids, one triterpenoid, one iridoid glycoside, and four others reported of Ajuga nipponensis, were summarized and discussed. Three main active components (12, 29, 54 ) were analyzed based on network pharmacology. The inflammatory signaling pathways were predicted by GO annotation analysis, and six key inflammatory targets were obtained. Molecular docking results showed that compounds 12, 29, and 54 had strong interactions with target proteins AKT1, TP53, PPARG, CASP3, and PTGS2. In particular, compound 54 has strong hydrogen bonding and conjugation with amino acid residues Met348, Met364, Val339, Leu353, Cys285, Ile262, Ile341, Ser342, and Arg288 in the active region of PPARG, and compound 29 has strong hydrogen bonding and alkylation with the amino acid residues Arg207, Leu168, Trp200, Phe256, Tyr204, Cys163, His121, and Met61 in the active region of CASP3. Graphical abstract: Three active ingredients 12, 29, and 54 were screened from Ajuga nipponensis . Their anti-inflammatory effects were analyzed by molecular docking with target proteins AkT1, TP53, PPARG, CASP3, PTGS2, and MMP9. Compound 54 has strong hydrogen bonding and conjugation with amino acid residues in the active region of PPARG, and compound 29 has strong hydrogen bonding and alkylation with the amino acid residues in the active region of CASP3. The chemotaxonomic and molecular biological significance of the active compounds were discussed. Image 1 Highlights: Sixty-one compounds were from Ajuga nipponensis. Compounds 12, 29, and 54 showed anti-inflammatory activity. AkT1, TP53, PPARG, CASP3, PTGS2, and MMP9 were found as anti-inflammatory targets. Compounds 12, 29, and 54 had strong interactions with anti-inflammatory proteins. Chemotaxonomic and biomolecular significance of the active compounds were discussed.